Strategi Pengembangan Potensi Wilayah Agroindustri Perkebunan Unggulan - Herdhiansyah, Dhian; Sutiarso, Lilik; Purwadi, Didik; Taryono, T (Jurnal Teknik Industri, 2012)
The development of plantation agro-industry should refer to primary commodity approach. Until now there is no accurate reference for government Kolaka. The diversifications of products and by-product have not developed yet. The objectives of this research were to formulate development strategy of regional potential of the prime plantation agro industry. The object of this research is six primary commodities of plantation; those are cacao, clover, pepper, cashew, coconut, and coffee in Kolaka Regency with Delphi and SWOT methods. The research results showed that the development strategy of regional potential of the prime plantation agro industry there are at quadrant I or that strategy was created by using all the power to take advantage of opportunities that an aggressive strategy by doing independence improvement of the farmers through development and counseling, partnership development on agro-industry activities in the effort of giving additional value of production.Â